Análise das manifestações patológicas nos sistemas de revestimentos externos - Pacheco, Clarisse Pereira (2016)
The lost of performance of external coating is meaninful when there is no apropriate project, a proper execution, quality materials and when maintenance is not performed by skilled professionals. These factors, together with the fact that the facade is very exposed to an outdoor aggressions, contribute to the appearence of pathological manifestations. In order to stop these damages and keep the useful life of the building, scheduled maintenance should happen according to findings obtained by building inspections. This work proposes a methodology to inspect painted plaster facades or with ceramic and the aplication of this method to inspect six buildings in Vitória, Espírito Santo state. Half of the buildings were made of painted mortar (ARG1, ARG2, ARG3) and the other half were made with ceramic (CER1, CER2, CER3). Pre-strutured models were used for inspection and for obtaining the parameters in order to analyse the deterioration of the facade. Through visual inspection of the facades, the damaged areas were mapped according to the region (continuous walls, openings, balconies, corners and ends, joints, transition between floors, roof) and cardinal orientation of the facade. The obtained data were used to calculate the Pathological Manifestation Index, the percentage of occurrence and the levels of degradation. Percussion test were made in the ceramic coating and in the ceramic plaques were performed the water absortion and expansion by moisture tests. In the buildings with mortar and paint there were the pipe method. Relevant informations concerning the buildings were obtained with interviews. This work concludes that the obtained data leads to the formulation of a more accurate diagnosis and that the methodology helped in getting these results.